America's Galapagos : the historic Channel Islands survey - Laverty, Corinne Heyning (The University of Utah Press, 2019)
"Laverty has researched and written about the Channel Islands Biological Survey conducted just prior to World War II off the coast of southern California and aborted due to the war and island location. The manuscript illuminates the scientific process and delves into the realities and difficulties of scientific fieldwork in the late 1930s. It also tells the behind-the-scenes story of the work of a natural history museum. The eight Channel Islands each support different ecosystems, both flora and fauna, and human histories. Five of the eight islands comprise Channel Islands National Park. The expedition researchers--John Adams Comstock, Art Woodward, Jack von Bloeker Jr., and Don Meadows--hoped to achieve the exhilaration and recognition from new discoveries but were thwarted by the war and their inability to complete and publish the survey data. However, early archaeology done on the islands, some by the biological survey crew, initiated on-going work there. Prehistoric sites found on the islands have less pothunting and destruction than those on the mainland, hence they are more productive for addressing numerous questions. Today, they are helping to answer questions about the routes and timing for the peopling of the Americas"--Provided by publisher.